Clinico-Immunological Profile of a 67-Year-Old Woman Affected by HER2-Positive Breast Cancer and Autoimmune Dermatomyositis - Pellegrino, Benedetta (Front Oncol, 2020)
A patient with HER2-positive early breast cancer (BC) developed dermatomyositis (DM), which disappeared after the first administration of adjuvant trastuzumab. No HER2 overexpression/amplification was observed in DM skin biopsies. Both BC and skin immune infiltrates were composed mostly of CD3+ T-lymphocytes. Interestingly, tumor-infiltrating lymphocytes expressed PD-1, which was negligible in skin-infiltrating lymphocytes, while both BC cells and keratinocytes were PD-L1-positive. High serum levels of endogenous anti-HER2 antibodies were detected, confirming the induction of a HER2-specific adaptive immune response. It may be argued that HER2-specific T-lymphocytes cross-reacted with one or more unknown skin antigens, causing DM. Trastuzumab may have silenced skin cross-reaction by eliminating any residual HER2-positive micrometastatic disease and, thus, inducing DM remission.